The road to victory the untold story of World War II's Red Ball Express - Colley, David P. (Warner books, 2001)
The true story of a bunch of tough-as-nails drivers who, during three pivotal months of World War II, operated the "Red Ball Express", is told through firsthand accounts. Almost all African Americans, these truckers rushed fuel and supplies to the rapidly advancing American armies desperately needed after D-Day to crush the German Panzers.